Nova Finishing Services / Erni Karni Mohamed Sujak … [et.al.] - Mohamed Sujak, Erni Karni; Salahuddin Aminy, Fatin Syahirah Aminy; Pinso, Jillian Jayce; Laku, Vimelia (2012)
Our company name is Nova Finishing Services. The business of our company has been decided on the form of partnerships. Each partner has contributes certain amount of capital as agreed in our agreement. Our main business activity is to offers services by providing finishes services in terms of tilling and ceiling. All partners are encourage and entitled to participate in all business management. We have agreed that Jillian Jayce Pinso as the General Manager and the Marketing Manager is Erni Karni bte. Mohamed Sujak, Fatin Syahirah Aminy bte Salahuddin Aminy as the Operational Manager and Administration Manager and Vimelia Anak Laku as the Financial Manager. The selection of General Manager is based on consensus among all the partners and selected based on the criteria of experience, skills and abilities.